ChemInform Abstract: Regioselective Synthesis of Substituted 4‐Alkylamino and 4‐Arylaminophthalazin‐1(2H)‐ones. Issue 28 (June 2016) - Krishnananthan, Subramaniam; Smith, Daniel; Wu, Dauh‐Rurng; Yip, Shiuhang; Gunaga, Prashantha; Mathur, Arvind; Li, Jianqing
Abstract: starting from 2‐formylbenzoic acids